International human rights law : cases, materials, commentary - Schutter, Olivier De (Cambridge : Cambridge University Press, 2014)
The leading textbook on international human rights law is now better than ever. The content has been fully updated and now provides more detailed coverage of substantive human rights, along with new sections on the war on terror and on the progressive realization of economic and social rights, making this the most comprehensive book in the field. It has a new, more student-friendly text design and has retained the features which made the first edition so engaging and accessible, including the concise and critical style, and questions and case studies within each chapter, as well as suggestions for further reading. Written by De Schutter, whose extensive experience working in the field and teaching the subject in both the US and EU gives him a unique perspective and valuable insight into the requirements of lecturers and students. This is an essential tool for all students of international human rights law.
The emergence of international human rights -- State responsibility and 'jurisdiction' -- The typology of States' obligations and the obligation to respect human rights -- The application of human rights in private relationships and the obligation to protect -- The progressive realization of human rights and the obligation to fulfil -- Derogations in time of public emergency -- The prohibition of discrimination -- Ensuring compliance with international human rights law : the role of national authorities -- The United Nations human rights treaties system -- The United Nations charter-based monitoring of human rights -- Regional mechanisms of protection.
Title from publisher's bibliographic system (viewed on 29 May 2018).
Keywords: elektronické knihy; electronic books; Human rights; International law and human rights